Improved electronic structure and magnetic exchange interactions in transition metal oxides. (5th October 2017) - Gopal, Priya; De Gennaro, Riccardo; Gusmao, Marta Silva dos Santos; Al Rahal Al Orabi, Rabih; Wang, Haihang; Curtarolo, Stefano; Fornari, Marco; Buongiorno Nardelli, Marco
Abstract: We discuss the application of the Agapito Curtarolo and Buongiorno Nardelli (ACBN0) pseudo-hybrid Hubbard density functional to several transition metal oxides. For simple binary metal oxides, ACBN0 is found to be a fast, reasonably accurate and parameter-free alternative to traditional DFT  +   U and hybrid exact exchange methods. In ACBN0, the Hubbard energy of DFT  +   U is calculated via the direct evaluation of the local Coulomb and exchange integrals in which the screening of the bare Coulomb potential is accounted for by a renormalization of the density matrix. We demonstrate the success of the ACBN0 approach for the electronic properties of a series technologically relevant mono-oxides (MnO, CoO, NiO, FeO, both at equilibrium and under pressure). We also present results on two mixed valence compounds, Co3 O4 and Mn3 O4 . Our results for these binary oxides and all the materials we have investigated, obtained at the computational cost of a standard LDA/PBE calculation, are in excellent agreement with hybrid functionals, the GW approximation and experimental measurements.